2018
DOI: 10.3390/sym10120679
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Asymmetry of Brain and Behaviour in the Zebra Finch, Taeniopygia guttata

Abstract: Lateralisation of eye use indicates differential specialisation of the brain hemispheres. We tested eye use by zebra finches to view a model predator, a monitor lizard, and compared this to eye use to view a non-threatening visual stimulus, a jar. We used a modified method of scoring eye preference of zebra finches, since they often alternate fixation of a stimulus with the lateral, monocular visual field of one eye and then the other, known as biocular alternating fixation. We found a significant and consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
4
7
0
Order By: Relevance
“…For instance, a rightward bias in the integration of visual and olfactory non-social cues has been found in chicks [84]. In zebra finches, several cases of a lateralization pattern have been demonstrated by both, behavioural and IEG-expression studies, which are compatible with that found in other species (reviewed in [85]). This includes a right hemisphere specialisation for monitoring threatening stimuli [85], a left hemisphere specialisation for controlling foraging behaviour [86] and complementary specialisation of the two hemispheres for different aspects of song processing [87][88][89].…”
Section: Discussionsupporting
confidence: 60%
“…For instance, a rightward bias in the integration of visual and olfactory non-social cues has been found in chicks [84]. In zebra finches, several cases of a lateralization pattern have been demonstrated by both, behavioural and IEG-expression studies, which are compatible with that found in other species (reviewed in [85]). This includes a right hemisphere specialisation for monitoring threatening stimuli [85], a left hemisphere specialisation for controlling foraging behaviour [86] and complementary specialisation of the two hemispheres for different aspects of song processing [87][88][89].…”
Section: Discussionsupporting
confidence: 60%
“…Intriguingly, lateralization has long since been controversial in the zebra finch, which produces songs with a rich spectro-temporal structure. A recent study reported that the left (right) hemisphere is superior in auditory processing of the temporal (spectral) feature of songs [36], which is consistent with the general directional asymmetry in visual processing [37]. The left hemisphere is dominant for the auditory perception of vocal communication in mice [38] and rats [39].…”
Section: Left-right Brain Asymmetry In Non-human Animalssupporting
confidence: 58%
“…The preference shown by zebra finches to use the right eye when courting a female would, at first sight, appear to contradict specialization of the left-eye-system for control of copulation, as found in the chick. However, as we have argued previously [40], courtship involves different control by the forebrain than does copulation. In fact, courtship behaviour requires inhibiting the actual copulation response.…”
Section: Studies Of Lateralization Conducted In Laboratory Settingsmentioning
confidence: 60%
“…Firstly, zebra finches display the same ability as chicks to discriminate grain from pebbles only when they use their right, and not their left, eye [39]. Secondly, zebra finches have been reported to show a preference to use the left eye when looking at a predator, as chicks also do [40]. Interestingly, Workman and Andrew [41] reported that, during courtship, males of this species prefer to approach females so that they view them with their right eye.…”
Section: Studies Of Lateralization Conducted In Laboratory Settingsmentioning
confidence: 99%
See 1 more Smart Citation